2020
DOI: 10.1002/adma.201907786
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing Perovskite Light‐Emitting Diodes by Incorporation of Binary Alkali Cations

Abstract: high-performance LEDs due to high photoluminescence (PL) quantum efficiency, narrow emission linewidth (i.e., high color purity), and low density of sub-gap electronic trap states. [6][7][8][9] Significant breakthroughs have been achieved in perovskite LEDs (PeLEDs) in the past 5 years, with the external quantum efficiency (EQE) boosted from 0.76% in 2014 to over 21% recently, [1,10,11] comparable to the stateof-the-art performance of organic LEDs (OLEDs). [12] Nevertheless, despite rapid development of electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 54 publications
4
69
0
1
Order By: Relevance
“…This generalized template is consistent with other recent strategies successfully stabilizing PeLED operation including use of 2D molecules and Cs/Rb components. [26,40] In conclusion, using a combination of in-and ex situ device, nanoscale cross-sectional chemical mapping, and optical spectroscopy measurements, we found that the reduction in the performance and luminescence yield of (Cs 0.06 FA 0.79 MA 0.15 ) Pb(I 0.85 Br 0.15 ) 3 PeLED devices arises from an accumulation of bromide content at one interface and a more iodide-rich bulk material. This accumulation of ions leads to a defective perovskite layer that acts as an injection barrier for charge carriers and leads to increased nonradiative recombination.…”
mentioning
confidence: 80%
See 3 more Smart Citations
“…This generalized template is consistent with other recent strategies successfully stabilizing PeLED operation including use of 2D molecules and Cs/Rb components. [26,40] In conclusion, using a combination of in-and ex situ device, nanoscale cross-sectional chemical mapping, and optical spectroscopy measurements, we found that the reduction in the performance and luminescence yield of (Cs 0.06 FA 0.79 MA 0.15 ) Pb(I 0.85 Br 0.15 ) 3 PeLED devices arises from an accumulation of bromide content at one interface and a more iodide-rich bulk material. This accumulation of ions leads to a defective perovskite layer that acts as an injection barrier for charge carriers and leads to increased nonradiative recombination.…”
mentioning
confidence: 80%
“…Passivation with alkali metals such as potassium have been previously shown to reduce nonradiative losses and ion migration in perovskite devices. [ 29–40 ] We prepared a series of passivated perovskite thin films by addition of different amounts of potassium iodide solution (in the range x = 0–0.44, where x is the fraction of potassium out of total monovalent cations; [K]/([K] + [MA] + [FA] + [Cs])) to different iodide/bromide composition solutions to explore the series (Cs 0.06 FA 0.79 MA 0.15 )Pb(I 1− y Br y ) 3 , with y = 0–1 being the fraction of bromide out of total halide (with corresponding PL emission peaks spanning 560 to 826 nm, see Figure S7, Supporting Information). To assess the resilience of the resulting films to photo‐induced ion migration, we monitored the PL spectra of the films before and after continuous illumination at ≈60 mW cm −2 over a period of 30 min.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…In response to the instability issue under electric eld, various strategies have been developed to improve the lifetime, while the T 50 exceeding one hundred hours is rarely reported, lagging far behind that of perovskite solar cells, which can be closely related to the higher working bias required for PeLEDs. Degradation mechanism studies demonstrate that ion migration in perovskite structure, Joule heating and instability of injection layers under electric eld are the main causes of the poor stability [13][14][15][16] . The severe ion drift in perovskite upon electric eld during operation results in the emission wavelength shift 17 , the decomposition of perovskite layer 18 , the interfacial reaction between perovskite and injection materials/electrode layers 14,19 , giving rise to a completely irreversible degradation after prolonged operation.…”
Section: Introductionmentioning
confidence: 99%